2015
DOI: 10.1021/jacs.5b06379
|View full text |Cite
|
Sign up to set email alerts
|

Selective Cation Exchange in the Core Region of Cu2–xSe/Cu2–xS Core/Shell Nanocrystals

Abstract: We studied cation exchange (CE) in core/shell Cu2–xSe/Cu2–xS nanorods with two cations, Ag+ and Hg2+, which are known to induce rapid exchange within metal chalcogenide nanocrystals (NCs) at room temperature. At the initial stage of the reaction, the guest ions diffused through the Cu2–xS shell and reached the Cu2–xSe core, replacing first Cu+ ions within the latter region. These experiments prove that CE in copper chalcogenide NCs is facilitated by the high diffusivity of guest cations in the lattice, such th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
86
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 33 publications
1
86
0
Order By: Relevance
“…Established by recent studies published in the literature for cation exchange reactions at single nanocrystals, the copper chalcogenide phase was used as an intermediate for further cation exchange reactions. 31,[39][40][41] To show the reversibility of the cation exchange, the copper chalcogenide acetogels were also exchanged back to CdSe/CdS NR and CdS NR acetogels and heated for several weeks to recover their original fluorescence properties. 39 Microscopic characterization techniques (SEM and TEM) were performed in order to analyse the morphological changes in the aerogel structures due to the cation exchange reactions.…”
Section: Reversible Cation Exchange On Cdse/cds Nr and Cds Nr Based Gmentioning
confidence: 99%
See 1 more Smart Citation
“…Established by recent studies published in the literature for cation exchange reactions at single nanocrystals, the copper chalcogenide phase was used as an intermediate for further cation exchange reactions. 31,[39][40][41] To show the reversibility of the cation exchange, the copper chalcogenide acetogels were also exchanged back to CdSe/CdS NR and CdS NR acetogels and heated for several weeks to recover their original fluorescence properties. 39 Microscopic characterization techniques (SEM and TEM) were performed in order to analyse the morphological changes in the aerogel structures due to the cation exchange reactions.…”
Section: Reversible Cation Exchange On Cdse/cds Nr and Cds Nr Based Gmentioning
confidence: 99%
“…1,3,29 In the recent past, different working groups investigated cation exchange reactions on nanocrystals with different shapes and material composition. [30][31][32][33][34][35] Due to the short diffusion path of the cations within the nanoparticle crystal, even cation exchange reactions which are unknown (or extremely slow) on the bulk scale can occur. In nanoparticle systems, the cation exchange process can take place in the millisecond regime.…”
Section: Introductionmentioning
confidence: 99%
“…5(c). Rather than the further cation exchange occurring to the entire CuS nanoplates, the dark-contrast region emerged on the edges of nanoplates and from which it proceeded to the remaining volume, so that both the interfacial energy and the elastic strain between the two different domains are minimized [35,36]. The major reaction steps in the formation of Pd-dispersed CuS nanoplates (Fig.…”
Section: Tracing the Formation Process And Mechanistic Studiesmentioning
confidence: 99%
“…Crystal engineering of colloidal semiconductor nanocrystals (CSNCs) to control electronic impurities doping and the hetero-interface to metal nanoparticles are critical for their real optoelectronics and photonic applications, [1,2] such as solid-state lighting, [3] lasing, [4] photovoltaics, [5,6] photodetection, [7] and sensors. [8] Despite the progress made with regards to composition and crystallinity control, [9] efficient aliovalent doping and highly curved heterostructuring to metal in the nanoscale are critical and still remain abig challenge.Cation exchange conversion of CSNCs has been exploited as ap otential crystal engineering strategy for precisely controlling the morphology,c omposition and crystallinity.…”
mentioning
confidence: 99%
“…[8] Despite the progress made with regards to composition and crystallinity control, [9] efficient aliovalent doping and highly curved heterostructuring to metal in the nanoscale are critical and still remain abig challenge.Cation exchange conversion of CSNCs has been exploited as ap otential crystal engineering strategy for precisely controlling the morphology,c omposition and crystallinity. [1][2][3][4] The groups of Alivisatos,M anna, Schaak, Zhang,K im, and Pradhan [7,8,[10][11][12][13][14][15][16] have taken such advantages to synthesize CSNCs.Wehave reported that tertiary phosphines (R 3 P) with different Rg roups could initialize cation exchange reactions to precisely tune the targeted CdX (X = S, Se etc. )N Cs crystallization, dopant concentration, and hetero-interface to Au NCs.…”
mentioning
confidence: 99%